The inter-relationship between body composition, physical activity and fitness in children - Hussey, Juliette (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Physiotherapy, 2007)
There is growing concern about the epidemic of childhood obesity and its associated health consequences. Contributing factors to this epidemic may be reduced levels of physical activity and increased levels of physical inactivity. Recommended guidelines for physical activity in children have increased but one could question if they are adhered to and if they are adequate. Studies, in children, investigating the relationship between body composition and physical activity have used a number of different methods to measure physical activity. In adults fitness appears to be related to a healthy body composition but this area has not been extensively addressed in children. The overall aim of this thesis was to investigate the relationship between body composition, physical activity levels and fitness in children.
Keywords: Physiotherapy, Ph.D.; Ph.D. Trinity College Dublin